Comparative genetic analysis of NS gene recombinant influenza vectors Flu-NS1-80-L7/L12 (H5N1) and Flu-NS1-124-L7/L12 (H5N1), expressing brucellosis antigen (Experimental biology, 2015)
This article presents the results of a comparative genetic analysis of NS gene of recombinant influenza vectors Flu-NS1-80-L7/L12 (H5N1) and Flu NS1-124-L7/L12 (H5N1) 1 and 6 of the passage levels, expressing the brucellosis ribosomal protein L7 / L12. Recombinant viruses Flu-NS1-80 L7/L12 (H5N1) and Flu-NS1-124-L7/L12 (H5N1) were designed by co transfection in Vero cells culture, then were adapted by 10 per diem developing chick embryos . The results of sequencing and subsequent Comparative analysis of NS gene sequence of recombinant strains confirmed the presence of brucellosis insertion L7/L12. Further research showed that the nucleotide sequence of the NS gene of recombinant viruses Flu-NS1-80-L7/L12 (H5N1) and Flu-NS1-124-L7/L12 (H5N1) 1 and 6 passage levels are genetically similar to each other and the degree of identity is 100 % , which proves the genetic stability of recombinant viral vectors for 6 consecutive passages
Keywords: recombinant viral vector; brucellosis antigen; reverse genetics; PCR (polymerase chain reaction); sequencing; genetic stability